Study on interaction mechanism between natural convection and forced convection during storage and temperature rise of waxy crude oil tank - Wei Sun; Yuduo Liu; Wenhua Xu; Lihui Kan; Hongfei Liu; Lixin Zhao; Zhihua Wang (Engineering Applications of Computational Fluid Mechanics)
As the primary facility for crude oil storage, storage tanks play a critical role in achieving high operational efficiency and low energy consumption through comprehensive understanding of complex thermal convection mechanisms. This study establishes a theoretical model for the coil-agitator synergistic heating process in crude oil storage tanks, characterizing the coupled heat transfer between natural and forced convection. Dimensionless parameters including Reynolds number, Grashof number, and Richardson number are employed to quantitatively delineate the agitator-induced forced convection zone, crude oil natural convection zone, and mixed convection region. Based on the spatial distribution characteristics of multi-scale turbulent vortex structures within these zones, the interaction mechanisms between natural and forced convection are qualitatively analyzed, while the Richardson number is used to quantitatively characterize the primary influencing factors of vortex flow in each convection region. The results indicate that the tank's heat transfer is dominated by coil-induced natural convection with supplementary agitator-driven forced convection. A 2.45 m² forced convection zone forms near the agitator. Reduced agitator rotation angle generates high-speed vortex flow along tank walls, forming large-scale vortex structures with enhanced intensity. This expands the forced convection zone by 55% and mixed convection zone by 73%, prolonging forced convection trajectories while improving natural convection heat exchange, albeit causing localized non-uniformity. Multi-scale analysis reveals that in the natural convection zone, large vortices (≥34.08 m) govern energy transport via macroscopic convection, while small-scale vortices (≤11.99 m) facilitate energy conversion through viscous dissipation. In forced convection regions, 30° agitator rotation optimally develops large vortices (≥8.52 m), enhancing vortex intensity while reducing energy dissipation. Furthermore, Richardson number analysis shows that large vortices (Ri ∈ [0, 10]) in the forced convection zone primarily enhance convective heat transfer, whereas small-scale turbulent vortices (Ri ∈ [0, 1]) contribute to mixing and heat transfer through localized energy dissipation.